2021
DOI: 10.1088/1755-1315/716/1/012104
|View full text |Cite
|
Sign up to set email alerts
|

Towards an eco-industrial development in West Papua economy

Abstract: West Papua province holds a crucial role to ensure the NDC target could be achieved in a measurable and timely manner. Despite its rich possession of pristine biodiversity, manufacture industry contributes 3% of the total provincial income. This study aims to predict the GRDP if West Papua incorporates Eco-Industrial Development (EID) to mitigate emissions from the industrial sector and its shares to the local community’s economy and the global economy. System dynamic modelling was employed to simulate and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…As a result, West Papua should manage its waste at a rate of no more than 118,297 tons per year in order to meet the target of 29% of the NDC. Wurarah et al (2021) found that the manufacturing industries in West Papua account for 3% of the GRDP. These industries will contribute 72,000 tons CO2e in 2030.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, West Papua should manage its waste at a rate of no more than 118,297 tons per year in order to meet the target of 29% of the NDC. Wurarah et al (2021) found that the manufacturing industries in West Papua account for 3% of the GRDP. These industries will contribute 72,000 tons CO2e in 2030.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A system dynamics model is capable of accepting system dynamics that require some interventions that need to be integrated throughout the simulation, increasing the model's complexity. Such models have been used successfully to help overcome problems of deforestation (Hendri et al, 2021), solid waste management (Prabawardani et al, 2021), eco-industry development (Wurarah et al, 2021), and electrical energy supply and demand (Oxa & Erma, 2012) as well as being used for analyzing and solving complex policy problems (Malbon & Parkhurst, 2022).…”
Section: Introductionmentioning
confidence: 99%